El Excentrico, 1975-08-20 - None::::::::::::::: (Garcia Printing; San Jose, California, 2023)
August 20, 1975. [20 de agosto de 1975]. No volume or issue number. Cover has group of people posing for the Club Felipe's 17th Anniversary Dance in San Jose, California.